Effectiveness of immediate bonding of etch-and-rinse adhesives to simplified ethanol-saturated dentin - Leandro Afonso Guimarães; Júlio César Franco Almeida; Linda Wang; Paulo Henrique Perlatti D'Alpino; Fernanda Cristina Pimentel Garcia (Sociedade Brasileira de Pesquisa Odontológica, 2012)
This study examined the immediate bond strength of etch-and-rinse adhesives to demineralized dentin saturated with either water or absolute ethanol. The research hypothesis was that there would be no difference in bond strength to dentin between water or ethanol wet-bonding techniques. The medium dentin of 20 third molars was exposed (n = 5). The dentin surface was then acid-etched, left moist and randomly assigned to be saturated via either water wet-bonding (WBT) or absolute ethanol wet-bonding (EBT). The specimens were then treated with one of the following etch-and-rinse adhesive systems: a 3-step, water-based system (Adper Scotchbond Multipurpose, or SBMP) or a 2-step, ethanol/water-based system (Adper Single Bond 2, or SB). Resin composite build-ups were then incrementally constructed. After water storage for 24 h at 37°C, the tensile strength of the specimens was tested in a universal testing machine (0.5 mm/min). Data were analyzed by two-way ANOVA and Tukey's test (a = 5%). The failure modes were verified using a stereomicroscope (40'). For both adhesives, no significant difference in bond strength was observed between WBT and EBT (p > 0.05). The highest bond strength was observed for SB, regardless of the bonding technique (p < 0.05). No significant interaction between adhesives and bonding techniques was noticed (p = 0.597). There was a predominance of adhesive failures for all tested groups. The EBT and WBT displayed similar immediate bond strength means for both adhesives. The SB adhesive exhibited higher means for all conditions tested. Further investigations are needed to evaluate long-term bonding to dentin mediated by commercial etch-and-rinse adhesives using the EBT approach.